Urbanization and Heat Island Effect: A Comparative Study in Egypt - Mohamed, Mostafa (International Journal of Climatic Studies, 2024)
Purpose: The aim of the study was to analyze urbanization and heat island effect: a comparative study Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A comparative study in Egypt investigated the impact of urbanization on the heat island effect. Findings indicated that highly urbanized areas, like Cairo, exhibited more pronounced heat island effects due to extensive infrastructure and limited vegetation. Rapid urbanization and land use changes were identified as significant contributors to increased heat island intensity. The study emphasizes the importance of urban planning strategies to mitigate these effects and calls for further research to better understand the urbanization-heat island relationship in Egypt. Unique Contribution to Theory, Practice and Policy: Theory of urban heat island effect, theory of land use and land cover change & theory of socioeconomic drivers of urbanization may be used to anchor future studies on urbanization and heat island effect: a comparative study. Integrate green spaces, such as parks, urban forests, and green roofs, into urban planning and design to mitigate the heat island effect. Implement urban planning regulations and building codes that mandate the incorporation of heat mitigation measures in new developments and retrofits.